2020
DOI: 10.2355/isijinternational.isijint-2019-747
|View full text |Cite
|
Sign up to set email alerts
|

Electroplating of Copper on Low Carbon Steel from Alkaline Citrate Complex Baths

Abstract: The use of alkaline electroplating baths is the essential requirement to deposit Cu directly onto steels because of non-adherent Cu formation by replacement reaction between Cu 2 + and Fe in acidic solution. For the development of such an electroplating bath, complexing agents to form soluble Cu complex in alkaline pH is necessary at first. Secondary, the soluble Cu complex must be reduced electrochemically. Cyanide-based baths meet these requirements, but the bath is toxic. In this study, the survey of comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…As liquids, we prepared water, 5 and 10 wt% NaCl solutions, 5 and 10 wt% NaNO 3 solutions, 5 and 10 wt% Cu(NO 3 ) 2 solutions and 5 and 10 wt% CuSO 4 solutions. NaCl solution and NaNO 3 solution are often used for ECM [ 23 , 24 , 36 , 37 ], and Cu(NO 3 ) 2 solution and CuSO 4 solution are used for electrochemical deposition of copper [ 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As liquids, we prepared water, 5 and 10 wt% NaCl solutions, 5 and 10 wt% NaNO 3 solutions, 5 and 10 wt% Cu(NO 3 ) 2 solutions and 5 and 10 wt% CuSO 4 solutions. NaCl solution and NaNO 3 solution are often used for ECM [ 23 , 24 , 36 , 37 ], and Cu(NO 3 ) 2 solution and CuSO 4 solution are used for electrochemical deposition of copper [ 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The objectives of this study were to verify the effects of electrolytes on the fabrication of LIPSSs since a few studies have reported that LIPSS geometry depends on the irradiation environment [ 31 ]. We also aimed to spheroidize copper since ECM can coat with copper using copper nitrate (Cu(NO 3 ) 2 ) solution and copper sulfate (CuSO 4 ) solution [ 32 , 33 , 34 , 35 ] since a long-pulsed laser or a continuous laser have been mainly used for laser enhanced electroless plating and the effects of an SPL on metal deposition with the fabrication of LIPSSs have never been studied. Experiments of laser irradiation with 1064 nm and 20 ps laser pulses at 0.04–1.0 J/cm 2 on the workpiece of 304 stainless steel under air, water, sodium chloride (NaCl) solution, sodium nitrate (NaNO 3 ) solution, copper nitrate (Cu(NO 3 ) 2 ) solution and copper sulfate (CuSO 4 ) solution, were conducted to fabricate LIPSSs in liquids and to change the surface composition.…”
Section: Introductionmentioning
confidence: 99%
“…The citrate can not only act as the supporting electrolyte of the plating solution, but also increase the cathodic reduction overpotential of copper ion and refine the grain of copper coating. Saeki et al [19] reported that the grains obtained from the citrate bath were finer and closer to each other than that of acidic sulfate Cu plating bath by SEM images of copper coatings with different thicknesses. Kim and Duquette [20] found that the concentration ratios of [Cu 2 + /Cit 3À ] controlled the morphologies of copper coatings in wafer trenches by AFM image study.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are problems associated with the copper coating process. The widely used copper-plating process uses cyanide ions, which can cause serious environmental pollution problems [ 27 , 28 ]. Other methods, such as plasma treatment with oxygen, chemical vapor deposition, and ammonia plasma, require complex equipment and procedures [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%